Odpowiedzi

Najlepsza Odpowiedź!
2010-02-10T19:37:01+01:00
A)2(-3a+b)+3(2a-3b)= -6a+2b+ 6a-9b= -7b
b)(4a-7b)4-7(2a-5b)-2(a+b)= 16a-28b-14a+35b-2a-2b=5b
c)-2(3x-2y+1)+4(-x+y-5)= -6x+4y-2-4x+4y-20=-22-10x+8y
d)6(2ab+3a-b)-8(4a-5b+9)-2(-ab+5)=12ab+18a-6b-32a+40b-72+2ab-10=14ab-14a+34b+30
2010-02-10T19:40:08+01:00
A)2(-3a+b)+3(2a-3b)= -6a+2b + 6a-9b=7b
b)(4a-7b)×4-7(2a-5b)-2(a+b)=16a-28b-14a+35b-2a-2b=5b
c)-2(3x-2y+1)+4(-x+y-5)=-6x+4y-2-4x+4y-20=10x+8y+22
d)6(2ab+3a-b)-8(4a-5b+9)-2(-ab+5)=
12ab+18a-6b-32a+40b+72+2ab+10=14ab+14a+34b+82


musisz tylko pamiętać o tym, że
+ i + = +
- i - = +
+ i - = -
- i + = - :)
2010-02-10T19:46:05+01:00
A)-6a + 2b + 6a -9b= -7b
b)4a - 7b*4 -14a +35 -2a-2b=4a-28b-14a+35b-2a-2b=-12a+5b
c)-6x+4y-2--4x+4y-20=-10x-22+8y
d) 12ab+18a-6b-32a+40b-72+2ab-10=14ab-14a+34b-82